Readiness model for requirements change management in global software development. Issue 10 (23rd April 2020) - Akbar, Muhammad Azeem; Mahmood, Sajjad; Huang, Zhiqiu; Khan, Arif Ali; Shameem, Mohammad
Abstract: Requirements Change Management (RCM) is one of the challenges faced by Global Software Development (GSD) organisations as requirements evolution is inevitable due to dynamic business and operating environments. GSD organisations face issues when dealing with RCM because many organisations embark on GSD without understanding their readiness to undertake such an initiative. Currently, there is no readiness model to assess the RCM process in the context of GSD. The objective of this study is to develop a requirements change management readiness model (RCMRM) for GSD organisations. A Systematic Mapping Study (SMS) was conducted to identify the primary studies related to RCM in the GSD projects. By using SMS, 109 primary studies were selected and 73 RCM practices were identified which were used to design the readiness levels of the proposed RCMRM. To validate the RCMRM, initially, two case studies were conducted in two GSD organisations. Based on the suggestions and recommendations of the case study participants, the RCMRM was further modified. The updated version of RCMRM was further validated by two different GSD organisations. The results of the second case study indicate that RCMRM is effective in assessing the readiness of the RCM process in the context of GSD.